PENGARUH PRODUK DOMESTIK BRUTO, INFLASI DAN RASIO GINI TERHADAP PENGANGGURAN TERBUKA DI PROVINSI DKI JAKARTA - Sri Mahendra Satria Wirawan (Jurnal Good Governance, 2018)
Gross Regional Domestic Product (GRDP) which provides a comprehensive picture of the economic conditions of a region is indicator for analyzing economic region development. Another indicator that is no less important is inflation as an indicator to see the level of changes in price increases due to an increase in the money supply that causes rising prices. The success of development must also look at the income inequality of its population which is illustrated by this ratio. One of the main regional development goals is to improve the welfare of its people, where to see the level of community welfare, among others, can be seen from the level of unemployment in an area. To that end, in order to get an overview of the effects of GRDP, inflation and the ratio of gini to unemployment in DKI Jakarta for the last ten years (2007-2016), an analysis was carried out using multiple linear regression methods. As a result, together the relationship between GRDP, inflation and the Gini ratio is categorized as "very strong" with a score of 0.936, and has a significant influence on unemployment. Partially, the GRDP gives a significant influence, but inflation and gini ratio do not have a significant influence. GDP, inflation and the Gini ratio together for the last ten years have contributed 81.4% to unemployment in DKI Jakarta, while the remaining 18.6% is influenced by other variables not included in this research model, so for reduce unemployment in DKI Jakarta, programs that are oriented to economic growth, suppressing inflation and decreasing this ratio need to be carried out simultaneously. Keywords: GRDP, inflation, unemployment, DKI Jakarta, GINI ratio